DAMPAK UNDANG-UNDANG CIPTA KERJA TERHADAP INVESTASI ASING: TINJAUAN HUKUM DAN PRAKTIS - Julita Sari, Ria (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
The Job Creation Law or Omnibus Law is a significant reform in Indonesian investment law that aims to increase the attractiveness of foreign direct investment (FDI) by simplifying regulations and providing legal certainty. To strengthen Indonesia's position in the global market, the Job Creation Law introduces the Online Single Submission (OSS) system to accelerate licensing and a positive investment list that opens up more sectors to foreign investors. This paper analyzes the impact of these policies on FDI flows with a focus on the technology and renewable energy sectors that received a significant boost from fiscal incentives and the grandfathering concept that protects investment from sudden policy changes. Despite positive results, implementing the Job Creation Law faces challenges, especially in harmonizing regulations between the central and regional governments. This article recommends improving incentives in strategic sectors and harmonizing regulations to optimize the benefits of the Job Creation Law so that Indonesia can achieve greater economic potential and increase its competitiveness on the international stage.